2005
DOI: 10.1111/j.1744-7909.2005.00163.x
|View full text |Cite
|
Sign up to set email alerts
|

Presowing Seed Treatment with Cytokinins and Its Effect on Growth, Photosynthetic Rate, Ionic Levels and Yield of Two Wheat Cultivars Differing in Salt Tolerance

Abstract: The effects of presowing seed treatment with different concentrations of cytokinins (kinetin and benzylaminopurine; 100, 150, and 200 mg/L) on growth, photosynthetic capacity, and ion homeostasis were investigated in two spring wheat (Triticum aestivum L.) cultivars, namely MH-97 (salt sensitive) and Inqlab-91 (salt tolerant). Primed and non-primed seeds were sown in a field in which NaCl salinity of 15 dS/m was developed. Of the different concentrations of priming agents tested, the effect of a moderate conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
31
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 30 publications
4
31
0
Order By: Relevance
“…Therefore, the exogenous application of kinetin is likely to diminish the effects of salt stress on the growth and grain yield of wheat cultivars. These results are in agreement with those of some other studies that have shown the kinetin-induced salt tolerance in wheat (Roth 1987;Iqbal and Ashraf 2005b). The effectiveness of kinetin-priming to promote later growth and development in the present studies suggested its application to the soils where plants are irrigated with saline water that affects later plant growth and hence yield severely.…”
Section: Discussionsupporting
confidence: 95%
See 2 more Smart Citations
“…Therefore, the exogenous application of kinetin is likely to diminish the effects of salt stress on the growth and grain yield of wheat cultivars. These results are in agreement with those of some other studies that have shown the kinetin-induced salt tolerance in wheat (Roth 1987;Iqbal and Ashraf 2005b). The effectiveness of kinetin-priming to promote later growth and development in the present studies suggested its application to the soils where plants are irrigated with saline water that affects later plant growth and hence yield severely.…”
Section: Discussionsupporting
confidence: 95%
“…Seed enhancement with PGRs has been successfully applied to counteract the deleterious effects of salinity on germination and plant growth (Debez et al 2001;Angrish et al 2001;Iqbal and Ashraf 2005b). Cytokinins are important signalling molecules in plants (Rashotte et al 2005) and interact with other plant hormones in the regulation of plant growth and development (Schmü lling et al 1997;Brault and Maldiney 1999).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6), in contrast to the enhanced salt tolerance of Arabidopsis ahp mutants (Nishiyama et al, 2013). In Arabidopsis, cytokinin appears to have both positive (Elkeltawi and Croteau, 1987;Gadallah, 1999;Iqbal and Ashraf, 2005;Iqbal et al, 2006) and negative (Tran et al, 2007) effects on salt tolerance, suggesting that the role of cytokinin is complex and that its influence depends on a variety of factors. The salt overly sensitive (SOS) signaling system increases plant salt tolerance by activating Na + -extrusion antiporters (Shi et al, 2002;Martínez-Atienza et al, 2007); the high-affinity K + transporter1;1 (OsHKT1;1), which mediates inward Na + transport (Jabnoune et al, 2009), protects young leaves from ion toxicity by the accumulation of Na + and Cl 2 in old leaves (Wang et al, 2012); and Na + /H + antiporter genes (OsNHXs) play roles in the compartmentalization of Na + into vacuoles (Fukuda et al, 2011).…”
Section: Osahp1 and Osahp2 Have Opposing Effects On Plant Sensitivitymentioning
confidence: 79%
“…With regard to presowing seed treatment, CYT have been demonstrated to promote germination, yield, and fiber properties of cotton (Sawan et al 2000), besides enhancing nitrogen metabolism and productivity of chickpea (Fatima et al 2008). Moreover, seed priming with kinetin has also been shown to counteract the adverse effects of salinity on germination of lettuce (Khan and Huang 1988), wheat (Afzal et al 2005), and sorghum (Ismail 2003), as well as growth, photosynthetic activity, ion contents and yield of wheat (Iqbal and Ashraf 2005). In this milieu, it is foreseeable that further elucidation of the effects of KIN pretreatment per se, especially on key enzyme activities, concurrent to photosynthetic and yield attributes, would provide valuable comparative information for tolerance-enhancing strategies focusing on presowing hormone supplementation.…”
Section: --mentioning
confidence: 98%